Correlation of Different Facial Measurements among Undergraduate Medical and Nursing students in Nepal (Janaki Medical College Journal of Medical Science, 2021)
Background and Objectives: The human being is found different by its overall morphology and body dimensions. Thus, the study was focussed to access the correlation of different facial measurements among undergraduate medical and nursing students in Nepal.Material and Methods: An institutional based cross-sectional study was carried out in the Department of Clinical Anatomy, Maharajgunj Medical Campus, Institute of Medicine, Kathmandu, Nepal. The variables selected for the present study was 140 subjects, among them 44 were female and 96 were male. Physical measurements were made by Spreading Caliper, Measuring tape, Weight machine, Height Scale. All the procedures were of non-invasive type. The personal height and weight, head length, head breadth, head circumference, Facial height, bigonial breadth, bizygomatic facial breadth was measured using International standard protocol. Statistical analysis was done using SPSS 20. ‘t’ tests was applied. P